Regioselective Zn(OAc)2-catalyzed azide–alkyne cycloaddition in water: the green click-chemistry; Organic Chemistry Frontiers; Vol. 4, iss. 6 - Morozova M. A. Mariya Aleksandrovna; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Kratochvil B. Bogumil; Eigner V.; Bondarev A. A. Aleksandr Aleksandrovich; Yoshimura A. Akira; Saito A. Akio; Zhdankin V. V. Viktor Vladimirovich; Trusova M. E. Marina Evgenievna; Postnikov P. S. Pavel Sergeevich (2017, 2017)
Title screen